SDL 2015 : model-driven engineering for smart cities : 17th International SDL Forum, Berlin, Germany, October 12-14, 2015 : proceedings /: model-driven engineering for smart cities : 17th International SDL Forum, Berlin, Germany, October 12-14, 2015 : proceedings. (2015) - Unknown
No abstract available